Invitro Antidiabetic Activities of Agar, Agarosa, and Agaropectin from Gracilaria gigas Seaweed - H. Hardoko; Agnes Febriani; Titri Siratantri (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Some types of seaweed are reported to have antidiabet activity in vivo or in vitro,but the activity antidiabet fractions of polysaccharides from seaweed has not been widelyreported. Gracilaria gigas is one type of red seaweed that can produce agar and it has twofactions, namely agarose and agaropectin. The aim of this study was to obtain an agarextract, agarose fraction, agaropektin fraction of Gracilaria gigas and to determine theα-glucosidase inhibitory activity of extracts and the fractions. Extraction of agar that usedan ethanol solution, and to fractionate agarose and agaropektin used dimetilsulfoxidesolution. The results showed that the fraction of the agarose having lower sulfate content(0.28%) compared with agar (5.91%) and agaropektin (6.07%). Types of samples (agar,agarose, and agaropektin) and sample doses significantly in inhibiting α-glucosidaseenzyme activity. Agarose fraction has IC50 value against α-glucosidase lowest (96.86 ± 4.61ppm), followed by the extract agar (116.63 ± 5.61 ppm), then the fraction agaropektin(158.34 ± 1.77 ppm).Keywords: α-glucosidase, extract, fraction, Gracilaria gigas, IC50